2020
DOI: 10.3390/life10060094
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Use of Platelet-Rich Plasma in Knee Disorders and Surgery—A Systematic Review and Meta-Analysis

Abstract: In recent years, the interest in biological treatment of knee lesions has increased, especially the application of platelet-rich plasma is of particular note. The number of articles evaluating platelet-rich plasma (PRP) efficacy in the recovery of knee disorders and during knee surgery has exponentially increased over the last decade. A systematic review with meta-analyses was performed by assessing selected studies of local PRP injections to the knee joint. The study was completed in accordance with 2009 Pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 113 publications
1
24
0
Order By: Relevance
“…Similar findings were evidenced in a meta-analysis of six studies (111 procedures), in which PRP augmentation did reduce the risk of failure (from 25.7% to 9.9%) [ 60 ]. In 5323 procedures (83 studies), PRP resulted in better outcomes following meniscectomy [ 61 ]. Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were evidenced in a meta-analysis of six studies (111 procedures), in which PRP augmentation did reduce the risk of failure (from 25.7% to 9.9%) [ 60 ]. In 5323 procedures (83 studies), PRP resulted in better outcomes following meniscectomy [ 61 ]. Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In pooled estimates, there was no statistically significant difference noted for adverse events of PRP therapy compared to the control group (placebo, HA, corticosteroids, and mesenchymal stem cells). Multiple injections were also shown to be superior to a single injection, but this effect was only observed when three injections were applied [ 78 ]. Similar results regarding the frequency of PRP injections were shown in a meta-analysis by Vilchez-Cavazos and colleagues, where no difference in pain improvement was observed for single versus multiple PRP injections; however, there was a significant difference in functional outcomes at 6 months’ follow-up for a triple versus a single injection [ 79 ].…”
Section: Intra-articular Injectionsmentioning
confidence: 99%
“…Such as transforming growth factor (TGF), fibroblast growth factor (FGF), insulin-like growth factor (IGF), platelet-derived growth factor (PDGF), and epidermal growth factor (EGF), with all having been proven to increase cell proliferation, fibroblastic differentiation, and ECM deposition. As a combination of these factors, PRP could induce mass release of growth factors within one hour following intra-articular administration, which seems a convenient and efficient tool, but related meta-analysis studies found no significant benefit for ACLR in the clinic [ 80 , 81 ].…”
Section: Stem Cell Therapy For Graft Regenerationmentioning
confidence: 99%